Responding to Online Reviews: Problem Solving and Engagement in Hotels. (February 2013) - Park, Sun-Young; Allen, Jonathan P.
Using online reviews in the co-creation of the service experience remains an attractive but elusive goal, based on case studies of how four high-end hotels in the western United States respond to customers' reviews posted on TripAdvisor. Chosen specifically because they represent two divergent approaches for responding to reviews, the two sets of hotels provide a springboard for further study of how hotels can interact with customers through social media. Two of the hotels regularly responded publicly to guest comments, whereas the other two almost never posted answers to guest complaints—even though they monitored and reacted to those complaints. A comparison of management styles from the two sets of hotels was disparate in the following three areas: perceived accuracy of online reviews, internal communications style, and the approach to using online reviews for management purposes. First, hotels that responded frequently considered posted reviews to be an honest gauge of consumer sentiment, whereas nonresponders believed that reviews represented only extremely positive or negative views. Second, frequent responders had a collaborative communication style that involved regular meetings and consultations, whereas the infrequent responders (IRs) met only as needed. Some of the IRs also typically relied on an external corporate manager to handle social media, whereas the frequent responders commonly used internal staff. Finally, while all the hotels viewed posted comments as one mechanism to identify and solve customer problems, only one hotel went beyond that to make customer reviews a part of a strategic approach to an ongoing relationship.